Influence of two fertilization regimes on the amounts of organic acids and phenolic compounds of tronchuda cabbage (Brassica oleracea L. Var. costata DC) - Sousa, C. (2008)
A phytochemical study was undertaken on tronchuda cabbage ( Brassica oleracea L. var. costata DC) cultivated under conventional and organic practices and collected at different times. Six organic acids (aconitic, citric, ascorbic, malic, shikimic, and fumaric acids) were identified and quantified by HPLC-UV. Qualitative and quantitative differences were noted between internal and external leaves. Analysis of the phenolics of the internal leaves was achieved by HPLC-DAD, and the phenolic profile obtained was revealed to be distinct from that of the external leaves. By this means were identified and quantified 11 compounds: 3- p-coumaroylquinic acid, kaempferol 3-O-sophoroside-7-O-glucoside, kaempferol 3- O-(caffeoyl)sophoroside-7- O-glucoside, kaempferol 3- O-(sinapoyl)sophoroside-7- Oglucoside, kaempferol 3- O-(feruloyl)sophoroside-7- O-glucoside, kaempferol 3- O-sophoroside, two isomeric forms of 1,2-disinapoylgentiobiose, 1-sinapoyl-2-feruloylgentiobiose, 1,2,2¢-trisinapoylgentiobiose, and 1,2¢-disinapoyl-2-feruloylgentiobiose. In general, internal leaves exhibited more constant chemical profiles.